Phonics Media Assisted Reading Gains in Dyslexic Elementary Learners: Peningkatan Kemampuan Membaca dengan Bantuan Media Fonik pada Siswa SD dengan Disleksia - Prasetya, Tita Nur; Wachidah, Kemil (Indonesian Journal of Education Methods Development, 2025)
General Background Reading literacy is a fundamental competence in elementary education and becomes more challenging for children with dyslexia who experience phonological processing difficulties. Specific Background Instructional media that connect graphemes and phonemes, such as phonics media, are considered supportive tools to facilitate early reading practice in inclusive classrooms. Knowledge Gap However, empirical classroom-based evidence using a single-subject experimental approach to document measurable reading progress among dyslexic learners remains limited. Aims This study aimed to determine whether phonics media could improve beginning reading skills of a dyslexic child in an inclusive elementary school setting. Results Using a quantitative single-subject pre-experimental design with interviews, pretest–posttest measures, and 13 observation sessions across baseline and intervention phases, reading scores increased from 40–50% during initial baseline to 70–100% during intervention and were maintained at 90–100% in the second baseline, indicating consistent upward trends and stable performance. Novelty The study provides detailed phase-based visual analysis of individual learning progress through baseline–intervention–baseline conditions within authentic classroom practice. Implications These findings suggest that phonics-based learning media can serve as practical instructional support for teachers in inclusive schools to assist dyslexic students’ early reading development and encourage active participation in literacy activities. Keywords: Phonics Media, Dyslexia, Beginning Reading, Single Subject Research, Inclusive Education Key Findings Highlights Scores rose progressively across thirteen structured sessions Skills maintained after withdrawal of treatment phase Classroom implementation feasible for special needs learners